2017
DOI: 10.1177/1010428317705762
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic implications of miRNAs in osteosarcoma chemotherapy

Abstract: Osteosarcoma is the most common primary bone cancer in young adults and adolescents. Drug resistance is the main cause leading to therapeutical failure. The mechanisms of drug resistance of osteosarcoma have not been fully understood. Notably, recent researches associate microRNA with drug resistance in osteosarcoma cells, raising the awareness that targeting microRNAs may help in chemotherapy success. In this review, we summarize the mechanisms linking microRNAs to drug resistance and ongoing researches on mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Osteosarcoma is a type of malignant tumor characterized by strong local invasiveness (14, 15). According to a study, osteosarcoma patients with metastasis have strong resistance to chemotherapeutics, and approximately 30% of patients have no sensitivity to chemotherapeutics, which leads to poor clinical prognosis (16).…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is a type of malignant tumor characterized by strong local invasiveness (14, 15). According to a study, osteosarcoma patients with metastasis have strong resistance to chemotherapeutics, and approximately 30% of patients have no sensitivity to chemotherapeutics, which leads to poor clinical prognosis (16).…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs and drug resistance relationships in osteosarcoma have been identified, which further broadens the knowledge of the structure and functions of miRNAs in the disease (33). It has been predicted that miRNAs will reverse chemotherapy resistance in future analyses (34). miR-216b is a member of the miR-216 cluster and is located on human chromosome 2p16.1 (35).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, et al17 found that miR-4443 depletion increases the sensitivity of epirubicin-resistant H1299 cells to epirubicin by decreasing the IC50 of epirubicin and inducing cell apoptosis and G0/G1 cell cycle arrest in non-small cell lung cancer. Additionally, previous studies have demonstrated that miRNAs are also correlated with chemosensitivity in osteosarcoma 18. For example, miR-125b was found to enhance chemosensitivity to cisplatin in osteosarcoma 19.…”
Section: Introductionmentioning
confidence: 89%